Kombinasi algoritma kriptografi vigenere cipher dengan metode zig-zag dalam pengamanan pesan teks - Faris Apriliano Eka Fardianto Faris; Febi Yanto Febi; Iwan Iskandar Iwan; Pizaini Pizaini (Computer Science and Information Technology, 2023)
The rapid development of technology makes it easier to get information quickly and easily. Some information is public and some are confidential. Confidential information certainly requires security in maintaining confidentiality by parties not interested in the information. There are many forms of personal information, one of which is information in the form of text. Providing security to text messages can be done with cryptographic techniques. Cryptographic techniques work by encrypting the original message (plaintext) into text that is difficult to understand (ciphertext), which usually contains no meaning. This research uses classical cryptography where the encryption technique uses the decryption key used the same as the encryption key at the time of encoding. This research uses vigenere cipher and zigzag cipher cryptographic algorithms. Vigenere cipher algorithm is a cryptographic technique that uses a word or sentence with the length of the key adjusting to the plaintext. In comparison, zigzag ciphers use transposition techniques from columns and rows. The use of two cryptographic algorithms at once is intended to provide super security, encryption with layered keys and cryptanalysts will be difficult in cracking the information that has been encoded. Testing is carried out by performing mathematical calculations from vigenere and zigzag algorithms first which are used as a basis for implementation into text encoding simulation systems. On the system that has been created gives the same result as mathematical calculations. In ciphertext cracking tests using the Boxentrix system cannot return plaintext in the absence of a predefined key. While in performance testing the time depends on the number of characters used, the more the number of characters, the encryption and decryption time also increases.